Gayo Lues Traditional Law Regarding Community Order for Visitors at Sarah Juli Hotel - Dewi Robiyanti; Zetria Erma; Yulkarnaini Siregar; Erwin Hamonangan Pane; Syabri (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
The prohibition of seclusion is an early prevention of adultery because the act of adultery basically starts from the things that lead to it. The ratification of Qanun No. 14 of 2003 concerning Seclusion at the beginning of the application of Islamic law in Aceh as a qanun in the field of jina>ya>t was not without reason, the selection of the qanun had at least two reasons. The first reason, the act of seclusion is a form of immorality (haram) in Islamic law and is very disturbing to the community but has not been handled properly. Second, the existence of euphoria within the community in the form of 'people's justice' against the types regulated in this qanun jina>ya>t, in order to avoid taking vigilantes in the midst of society, the Aceh Government ratified Qanun No. 14 of 2003 as a form of anticipation to various disturbances in Acehnese society.